MEMAHAMI KONSEP TOLERANSI BERAGAMA DALAM KEBERAGAMAN : DARI MODERASI BERAGAMA HINGGA PENGUATAN SOSIAL DI MASYARAKAT - Ilya Ilya; Mas'ula Mas'ula; Mainah Mainah; Maskuri Maskuri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Indonesia's massive diversity often triggers group friction if not systematically managed through a substantive understanding of religious moderation. This research focuses on the gap between the ideals of harmony and the social prejudice that still haunts the multicultural society in Pontianak City. Adopting the Participatory Action Research methodology, the 2025/2026 Doctoral Candidate Service program implemented strategic stages that included situational analysis in Kampung Bangka, faith development for converts, technical guidance for educational institution management, and a moderation seminar at the Public Service Mall. The main innovation lies in the active involvement of students in grounding the value of tolerance in strategic public spaces to bridge interfaith dialogue. The research findings indicate that institutional synergy between the government, academics, and community organizations successfully mobilized the participation of hundreds of citizens and significantly increased the effectiveness of partner institution governance. Quantitative data confirmed the attendance of hundreds of participants, who demonstrated high enthusiasm for collective social action and strengthened the capacity of conflict mediators. The main conclusion confirms that internalizing universal values ​​through direct emotional interaction and multicultural education can transform societal mindsets to become more inclusive. This dialogical approach has proven effective in strengthening social solidarity and national sovereignty within a framework of authentic tolerance, while also serving as an innovative reference model for developing sustainable national harmony in heterogeneous urban areas throughout Indonesia for the glory of a dignified national civilization.